Employer Satisfaction with Polytechnic Graduate: Comparison Between Industry Cluster - Husnira binti Hussin; Rusdi bin Rusli; Wan Mohd Zawawi bin Wan Yunus (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
Purpose: This paper aims to Employer Satisfaction with Polytechnic Graduate: Comparison Between Industry Cluster. Design/methodology/approach: The method used is statistic-descriptive and the design used is cross sectional. Findings: 2 hypotheses are while the other is accepted. Research limitations/implications: This study used two-step analysis: Kruskal-Wallis test was used to identify differences for three industry cluster; mechanical, electrical and civil engineering. Post Hoc test performs to identify the detail differences between each cluster. Practical implications: Results show that from the 2 hypotheses proposed. Originality/value: This paper is original. Paper type: This paper can be categorized as a case study.